PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR STATIKA SISWA KELAS X TEKNIK BANGUNAN SMK NEGERI 5 PADANG - 477-487 , Fadli Chandra (Universitas Negeri Padang, 2014)
Abstract This research aimstoreveal the comparative statics results of students Class X in learn building techniques are taught with cooperative learning model type Group Investigation and taught by Conventional models in SMK N 5 Padang. The population of this research are students of Class X Building Engineering Department SMKN 5 Padangas many 81 people. The sampling was done bycluster random sampling technique. Instrument used objectivetest. Data analysis used the t test. The research results showed cooperative learning model type Group Investigation on statics subjects provide better learning out comes than learning out comes using conventional methods. Average student learning out comes for the experimental classwas 82.66 whilethe control class 63.60. Ttest showed count value greater thant table was tcount=6.0508> ttable =1.6973at0.05significance level. This showed that there is asignificant differencein student learning out come susing cooperative learning model type Group Investigation using conventional method sonstatic ssubjects of Class X Building Engineering Department SMKN5 Padang. Keywords: Modelsof learning, learning outcomesstatics